Shrinkage as a potential mechanism of recurrent clinical events in patients with a large vulnerable plaque. Issue 8 (August 2019) - Liu, Xianglan; Sun, Changbin; Tian, Jiangtian; Liu, Xinxin; Fang, Shaohong; Xi, Xiangwen; Gu, Xia; Sun, Yong; Tian, Jinwei; Yu, Bo
Abstract : Aims: This study aimed to investigate the progression and vascular shrinkage of vulnerable plaque lesions with a plaque burden at least 70% among patients with coronary artery disease by optical coherence tomography (OCT) and intravascular ultrasound (IVUS). Methods: Fifty-six OCT-identified vulnerable plaques from 47 patients were included among coronary angiography-identified nonculprit/nontarget lesions. Serial IVUS images were used to assess plaque progression and vascular shrinkage. Results: Thirty-five small vulnerable plaques (plaque burden <70%, group A) and 21 large vulnerable plaques (plaque burden ≥70%, group B) were identified. The IVUS results at baseline show that mean plaque areas ( P < 0.001) and the percentage atheroma volume (PAV) ( P < 0.0001) were greater and the minimal lumen area ( P < 0.0001) was smaller in group B. The absolute and relative changes in the PAV and mean plaque area from baseline to follow-up were not significantly different. However, the lesions exhibited vessel shrinkage [the mean external elastic membrane (EEM) area ( P = 0.02) and mean lumen area ( P = 0.03) were significantly smaller in group B] from baseline to follow-up. Patients in group B also exhibited clinical events (recurrent angina symptoms) during the follow-up period. Positive correlations were found between changes in the mean plaque area and the mean EEM area in large vulnerable plaques ( r = 0.61, P < 0.0001) and between changes in the mean EEM area and the mean lumen area in large vulnerable plaques ( r = 0.61, P < 0.0001). Conclusion: Vulnerable plaque progression was not different between small and large vulnerable plaques. However, large vulnerable plaque lesions tended to exhibit vascular shrinkage, which is possible a cause of coronary artery lumen loss in patients with large vulnerable plaques. Abstract : Supplemental Digital Content is available in the text